Coconut-based Systems in the Philippines: Intensification and Diversification with Climate-Smart Agriculture - Manilay, Alessandro A.; Cabriole, Marie Aislinn; Itliong, Kirstein; Jordan, Ruel; Rosimo, Magnolia M.; Monville-Oro, Emilita; Barbon, Wilson John; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
To generate evidence on increasing household resilience to climate change through increased farm income while also generating social benefits, a Cost-Benefit Analysis (CBA) study was undertaken in 2021 by the International Institute of Rural Reconstruction (IIRR) with support from the International Research and Development Center (IDRC). For the Philippine component of the study, the study determined the financial and social benefits of raising native pigs and planting fruit trees and black pepper gained by the households from Guinayangan, Quezon and Ivisan, Capiz.